Increased Incidence of Endometrial Cancer Following the WHI: An Assessment of Risk Factors [18OP]. (May 2017) - Constantine, Ginger; Kessler, Grant; Goldstein, Steven R.
Abstract : INTRODUCTION: The US incidence of Type I Endometrial cancer (EC) dramatically increased following the Women's Health Initiative (WHI). While most cancer rates are decreasing, EC incidence increased from 2003 to 2013. EC rates were stable 1992 to 2002, prior to the announcement of WHI results. Potential etiologies for this increase are examined, including compounded hormone therapy use, which may not provide adequate endometrial protection. METHODS: EC incidence was obtained from Surveillance, Epidemiology, and End Result Program database from 1975 through 2013. The incidence of risk factors thought to be associated with EC, including age, obesity, race, number of menstrual cycles, gravidity and parity, metabolic syndromes (diabetes mellitus, PCOS), diet and exercise, and medications (hormone therapy including FDA-approved and unapproved [compounded] estrogens and progesterone, tamoxifen, and hormonal contraceptives) were evaluated and temporal trends were compared to EC trends. RESULTS: Endometrial cancer rates were constant from 1992 to 2002 in women 50-74 years of age, but have increased 2.5% annually with a 10% increase from 2006 to 2012 (test for trend 0.82). The greatest percentage of new cases was in women 55-64 years of age. Use of estrogen and progestin combinations have decreased while risk factors remained constant or decreased during the same time; however, obesity and compounded hormone use have increased coincident with the EC increase. CONCLUSION: EC increased post-2002 following the WHI, which may be multifactorial. The combination of an increase in obesity concurrent with decreasing exogenous progesterone and an increase in compounded hormone therapy is a public health issue requiring further evaluation.